HYBRIDE IMAGING IN ADVANCED MELANOMA: PET/CT in advanced melanoma - Grozdic Milojevic, Isidora (Medical Research, 2023)
Objective: To evaluate the usefulness of 18F-FDG PET/CT in patients with advanced melanoma.  Methods: This study included 264 consecutive melanoma patients  who were sent for the 18F-FDG PET/CT. The inclusion criteria were: histopathologically verified melanoma stage III or IV; absence of other malignancy / infection; glycemia ≤ 11 mmol/l. The final study population consisted of 220 patients. After the first 18F-FDG PET/CT, the follow-up was performed after 11.81±7.99 months, for therapy response evaluation. Results: Pathological 18F-FDG PET/CT  was present in 154 patients. Sensitivity of 18F-FDG PET/CT  was estimated as 99%, specificity as 47%. There was no statistically significant difference between 18F-FDG PET/CT findings and gender and MDCT examination (p> 0.05). 18F-FDG PET/CT upstaged 45% patients, especially these with widespread disease.  SUV max and inguinal disease localization  (in patients who had lower extremities as primary localization of disease) were associated with progression free survival (PFS)  (p < 0.05). SUV max (HR 1.03, ,p
Keywords: advanced melanoma; 18F-FDG PET/CT